The Role of Agricultural Extension in Agricultural Development and Its Barriers - Sadat, Asadullah; Shinwari, Saeedullah; Salihi, Mohammad Sadiq (Journal of Natural Sciences – Kabul University, 2024)
Agricultural development is very important for sustainable economic development. Through agricultural development can increase the agricultural production, food security, rural poverty reduction, and stable rural development. Agriculture extension is the fundamental of agriculture development, via it can improve technical and organizational skills and in farmer's production, finally a high quality level of the harvest is achieved. In world today extension plays an important role in the increase of agricultural products and sustainable rural development, it leads to the growth of the domestic economy of the villagers, Extension is very important in the field of food security and economic growth. Although extension is very effective for agricultural development but not enough attention has been paid to agricultural extension for the development of our country's agriculture. Considering this problem, the research has been designed with the aim of agricultural extension for the development of agriculture. To determine the obstacles in front of it. This is a descriptive-inferential research that is based on library procedures, the information is collected and analyzed from internal and external reliable books, articles and websites. The result of the research shows that through agricultural extension programs, the ability of farmers is increased, the production and quality of agricultural products is increased, the economic growth of farmers' families is caused, a standard solution is created for the problems of farmers, agriculture extension is for the development of agriculture. The main problems of agricultural extension are lack of financial security, lack of extension staff, lack of trust and communication, lack of coordination between agricultural extension and agricultural educational institutions, lack of regular policy, plan and support.